Registro ocular del Playerito Menor (Calidris minutilla Charadriiformes, Scolopacidae) en Uruguay - Heinonen, Sofía (1988)
The ocular observatÍon of Calidris minutilla on the Uruguayan coast is commented, thus including it in that countries avifauna.